A new computational model of large three-row roller slewing bearings using nonlinear springs. (October 2017) - Wang, Hua; He, Peiyu; Pang, Bitao; Gao, Xuehai
In order to improve the computational efficiency of load distribution of large three-row roller slewing bearing, a new computational model using nonlinear springs is presented in this paper. In this model, each roller is simulated by a group of nonlinear springs, which has the same load-deformation performance with solid roller–raceway contacts. Thus, equivalent finite element roller–raceway contact models were built to acquire the load-deformation performance and the solid roller experiments were carried out to validate the computational results. Then, the computational accuracy and efficiency using the nonlinear spring-based model were analyzed from three aspects, the maximal contact load, the root mean square errors, and computation time. The results show that a group of parallel springs can be used to replace the solid roller and simulate the line contact performance between the roller and raceway, but an equivalent nonlinear spring is not recommended because of the low computational accuracy, the greater the spring number, the higher the computational accuracy, and the computation time of nonlinear spring-based models is just about 3–4% of time of solid roller-based model, but the model complexity and establishment time of a group of nonlinear springs will increase with the number of springs increasing.